(untitled) (Conference on English Language Teaching, 2024)
Responding to the needs of English language learning in a university, this case study examines a technology utilization applied in English language classes by using a quiz application in learning English as a foreign language tailored to the needs of students in the classroom. The data for this study were collected from interviews with six students studying in the English department of an Islamic university in the city of Kudus where English is one of the foreign languages (EFL). To analyze the data, this study used a qualitative approach method with interview and documentation. The findings show that the use of quizizz apps in learning English as a foreign language in the classroom raises various discussions such as students’ perceptions that quizizz application is an interactive, effective, interesting and fun learning application for developing English learning. Particularly, students reported that the use of quizizz had an effect on vocabulary and grammar improvements. In addition, it fosters reading skills to students.